The effect of APOE4 on plasma and cerebrospinal fluid polyunsaturated fatty acids following DHA supplementation. (December 2021) - Yassine, Hussein N.; He, Xulei; Lee, Mitchell; Gomez‐Loarte, Sol; Evans, Jim E.; Oberlin, Sarah; Abdullah, Laila
Abstract: Background: Past studies indicate that APOE4 promotes a metabolic shift toward greater fatty acid usage. We have shown that APOE4 is associated with lower increase in cerebrospinal fluid (CSF) polyunsaturated fatty acids (PUFAs) following supplementation with triglyceride (TG) based DHA. The purpose of this study is to define the effect of APOE4 on plasma and CSF lipids using a comprehensive lipidomic analysis. Method: Plasma and CSF samples were obtained from the DHA Brain Delivery Pilot, a randomized clinical trial of DHA treatment (n=13) vs placebo (n=13) in non‐demented older participants (CDR ≤ 0.5, age> 55 years old) and stratified by APOE4. Participants were provided 2, 040 mg DHA daily in the form of TG‐DHA for six months. Result: Following supplementation, levels of phosphatidylcholine DHA (PC 38:6) and cholesterol ester DHA (CE 22:6) had the largest increase in CSF (p<0.0001). Using principal component analysis, changes in plasma TG (56:8), TG (58:10), ePE (40:8), TG (56:9), PC (40:6) and PC (38:6) had the strongest correlations with changes in CSF PC (38:6, p<0.001). Figure 1 shows Pearson correlation coefficients of all plasma and CSF lipids. Among all lipid species, changes in PUFA enriched TGs were significantly correlated between CSF and plasma. APOE4 had a significant effect on CSF TG (52:6) changes, with the mean increase in E4 carriers significantly (0.039 units) less than in E4 non‐carriers (p=0.0072) after adjusting for baseline levels and treatment group. Conclusion: Our findings demonstrate the first time the existence of PUFAs within a TG pool in CSF that correlates with the corresponding plasma TG pool, suggesting an exchange of TG particles at the CSF‐blood barrier. The effect of APOE4 on the metabolism of PUFAs is strongest on TG enriched PUFAs and supports their greater oxidation in APOE4. These findings help explain why APOE4 carriers are vulnerable to dietary omega‐3 deficiency, and less responsive to short term omega‐3 supplementation.